2010
DOI: 10.1586/erc.10.4
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoproteins and cardiovascular disease: 2010 update

Abstract: High-density lipoprotein-cholesterol (HDL-C) is a continuous inverse cardiovascular risk factor. The mechanisms by which HDLs protect against atherosclerosis are multiple. The major effect is thought to be reverse cholesterol transport, the mechanism by which excess cellular cholesterol is returned to the liver for excretion in the bile. HDLs also have pleiotropic roles: they decrease inflammation, prevent low-density lipoprotein oxidation, vascular endothelial cell apoptosis and thrombosis, and improve vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 78 publications
1
21
0
1
Order By: Relevance
“…Because HDL-cholesterol levels can drop following acute inflammatory stimuli (6), it has been suggested that low HDL cholesterol levels associated with obesity are a result of chronic, low-grade inflammation (6). HDL has several functions, including mediation of reverse cholesterol transport (7) and inhibition of inflammation (8)(9)(10)(11), oxidation (12,13), and endothelial activation (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Because HDL-cholesterol levels can drop following acute inflammatory stimuli (6), it has been suggested that low HDL cholesterol levels associated with obesity are a result of chronic, low-grade inflammation (6). HDL has several functions, including mediation of reverse cholesterol transport (7) and inhibition of inflammation (8)(9)(10)(11), oxidation (12,13), and endothelial activation (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of image techniques in epidemiological studies has shown that the atherosclerotic plaque progression in individuals with carotid estenosis was smaller in those that presented high levels of HDL-C [28]. Current knowledge is still, however, insufficient to recommend desirable levels [29,30].…”
Section: Hdl and Cardiovascular Risk In Humansmentioning
confidence: 99%
“…In the arterial wall, the removal C from macrophages by HDL may prevent its accumulation and transformation into foam cell, and thereby atherosclerosis [30,45]. The first stage of the reverse transport is the C efflux from the cells to the fraction pre-1 of the HDL, initiated by ABCA1-mediated C transport to lipid-poor APOA1.…”
Section: Functionality Of the Hdl Particlementioning
confidence: 99%
See 2 more Smart Citations